The Impact of Social Media Technologies on Adult Learning - Khalil Alsaadat (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Technology and social media have presented significant tools for adult learners to learn and advance continually. Fast technological advancements have enabled development of technologies used for learning. Expansion of various tools has given professors, educaters, trainers, instructers, many alternatives towards the implementation of the technology supported learning. The use of social media can improve adult learning outcomes and academic accomplishment. Social media is increasingly proven to be beneficial in adult learning and has a huge potential for adult education. This paper sheds some lights on benefits of social media for adult learners, this is incorporated through the review of previous work and some barriers that encounters social media for learning purposes. Also some social media models are reviewed to show the growth and effect of social media in adult learning context, and suggestions and recommendations are provided.